Chronic liver injury induced by drugs: a systematic review. (27th September 2015) - Stine, Jonathan G.; Chalasani, Naga
Abstract To examine the available literature and summarize what is known about chronic drug‐induced liver injury. We reviewed PubMed/MEDLINE through March 2015. We developed a MEDLINE search strategy using PubMed medical subject heading terms chronic liver injury, hepatotoxicity, drug‐induced liver injury, cirrhosis and chronic liver disease. We reviewed the reference list of included articles to identify articles missed in the database search. Chronic liver injury from drugs is more common than once thought with prevalence as high as 18% based on large national registries. Patients with cholestatic injury, age ≤65 years, and a long latency period (>365 days) are at increased risk. Of the most common drugs associated with drug‐induced liver injury, antibiotics (amoxicillin‐clavulanic acid, trimethoprim‐sulfamethoxazole, azithromycin) are most likely to cause chronic injury. The presence of autoantibodies is common with chronic DILI, however, it is not diagnostic nor is it specific to autoimmune‐like drug‐induced liver injury. Immunosuppressive therapy may be necessary for individual cases of autoimmune‐like drug‐induced liver injury where cessation of the drug alone does not result in resolution of injury, however, the lowest dose should be used for the shortest duration with careful attention to the development of side effects. The effectiveness of treament of cholestatic liver injury with corticosteroids or ursodiol remains unclear. Cases of drug‐induced fatty liver, nodular regenerative hyperplasia and peliosis hepatitis are less common subtypes of chronic drug‐induced liver injury that deserve special consideration. A high degree of clinical suspicion is required for the diagnosis of chronic drug‐induced liver injury and should be suspected in any patient with liver associated enzyme abnormalities that persist out past 6 months of initial presentation. Treatment with drug removal and/or immunosuppressive therapy appears to be effective for the majority of cases. More study into pharmacogenomics and personalized medicine may aid in predicting which patients will go on to develop chronic drug‐induced liver injury.